The teaching actions: indicative for a historical-critical pedagogical practice (Research, Society and Development, 2018)
The study in focus is presented as an experience report, result from activities developed in the Program for Scholarships for Beginner Teachers (PSBT) in the course of 2016. This academic work aims to reflect the results of application of a historical-critical planning about reading and writing in a municipal school in Ariquemes/RO, with a class of third year of Basic Education. Initially, was done a bibliographic review guided on historical-critical pedagogy, with Saviani (2008, 2011) and Gasparin (2012) as main authors. In the aftermath, a semi-structured interview with the teacher of class and 32 hours of observations were carried out, helping the class teacher. After the recognition of students and the knowledge already acquired for them on the theme, the interdisciplinary planning of 32 hours was elaborated. As of activities developed, is considered that the historical-critical pedagogy is an innovative method for the educational institutions, because it allows the appropriation of scientific expertise without ignoring their relationship with the everyday knowledge. The teaching actions developed on the basis of such pedagogy demonstrated their efficiency in teaching-learning, is perceived improvements in the quality of reading and writing of majority children, besides a greater interest in the lessons.